2018
DOI: 10.1007/s00170-018-2038-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the melt pool properties and thermal effects of multi-laser diode area melting

Abstract: This is a repository copy of Investigating the melt pool properties and thermal effects of multi-laser diode area melting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
(35 reference statements)
2
2
0
Order By: Relevance
“…This diffusion led to an increase in the geometry of the pool, known as remelting. After such cyclic accumulation, the diffusion depth of the molten pool was about four layers, i.e., 200 μm, as shown in Figure 12 (remelting temperature > 1672 K), which is the same as the geometric size of the molten pool measured in a previously reported experiment [ 29 ]. However, a special state appeared as the number of new layers increased, the remelting temperature decreased gradually, and the increase or decrease in temperature was less than that of the previous stage.…”
Section: Discussionsupporting
confidence: 74%
“…This diffusion led to an increase in the geometry of the pool, known as remelting. After such cyclic accumulation, the diffusion depth of the molten pool was about four layers, i.e., 200 μm, as shown in Figure 12 (remelting temperature > 1672 K), which is the same as the geometric size of the molten pool measured in a previously reported experiment [ 29 ]. However, a special state appeared as the number of new layers increased, the remelting temperature decreased gradually, and the increase or decrease in temperature was less than that of the previous stage.…”
Section: Discussionsupporting
confidence: 74%
“…Experimental results show some discrepancies, as some authors have concluded that thicker powder layers lead to slightly smaller MPs 37 , whereas some other authors have observed the opposite behavior 38 . Simulations agree with the latter results, as they point out that thicker layer thicknesses lead to higher peak temperatures 39 because the powder has a lower thermal conductivity than the bulk material solidified in bottom layers 40 , 41 . The effect of layer thicknesses on MP shape is even less clear.…”
Section: Discussionsupporting
confidence: 73%
“…Laser additive manufacturing is a technological method for the direct production or growing of functional objects from powders. Recent research [1][2][3][4] has aimed to create new classes of materials as gradient construction and functional materials (with gradient properties for different functional elements of geometrically complex parts), gradient reinforced by ceramics [5], variations of content for intermetallic alloys, adaptations of the method for hard-to-melt materials as hard alloys based on tungsten or tungsten itself, etc. [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%